Highly Dynamic Shape Memory Alloy Actuator for Fast Moving Soft Robots. Issue 4 (7th January 2019) - Huang, Xiaonan; Kumar, Kitty; Jawed, Mohammad K.; Mohammadi Nasab, Amir; Ye, Zisheng; Shan, Wanliang; Majidi, Carmel
Abstract: Shape memory alloys (SMAs) are popular as actuators for soft bioinspired robots because they are naturally compliant, have high work density, and can be operated using miniaturized on‐board electronics for power and control. However, SMA actuators typically exhibit limited bandwidth due to the long duration of time required for the alloy to cool down and return to its natural shape and compliance following electrical actuation. This challenge is addressed by constructing SMA‐based actuators out of thermally conductive elastomers and examining the influence of electrical current and actuation frequency on blocking force, bending amplitude, and operating temperature. The actuator is composed of a U‐shape SMA wire that is sandwiched between layers of stretched and unstretched thermal elastomer. Based on the studies, the ability is demonstrated to create a highly dynamic soft actuator that weighs 3.7 g, generates a force of ≈0.2 N, bends with curvature change of ≈60 m −1 in 0.15 s, and can be activated with a frequency above 0.3 Hz with a pair of miniature 3.7 V lithium–polymer batteries. Together, these properties allow the actuator to be used as an "artificial muscle" for a variety of tethered and untethered soft robotic systems capable of fast dynamic locomotion. Abstract : Shape memory alloy and thermally conductive rubber are combined to create an actuator that acts as an "artificial muscle" for a variety of tethered and untethered soft robots capable of dynamic locomotion. The actuator is shown to reliably produce rapid motion over consecutive activation cycles in response to electrical activation and is studied using both experimental and computational techniques.